2014
DOI: 10.1111/cea.12244
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of an oral CCR3 antagonist in patients with asthma and eosinophilic bronchitis: a randomized, placebo‐controlled clinical trial

Abstract: In conclusion, this study calls into question the role of CCR3 in airway eosinophilia in asthma and suggests that other cellular mechanisms mediated by the CCR3 receptor may contribute to airway hyperresponsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 40 publications
2
52
0
1
Order By: Relevance
“…CCR3 was previously shown to be a target in allergic disease, and various oral CCR3 antagonists have been developed [30][31][32][33] . Some of these antagonists have already been tested in clinical studies, and their safety has been confirmed in humans [32,33] . Although their targets are allergy-related diseases, based on the results of our present study, these oral CCR3 antagonists may have potential as a new therapeutic approach for retinal neovascularization, such as for diabetic retinopathy in the future.…”
Section: Discussionmentioning
confidence: 99%
“…CCR3 was previously shown to be a target in allergic disease, and various oral CCR3 antagonists have been developed [30][31][32][33] . Some of these antagonists have already been tested in clinical studies, and their safety has been confirmed in humans [32,33] . Although their targets are allergy-related diseases, based on the results of our present study, these oral CCR3 antagonists may have potential as a new therapeutic approach for retinal neovascularization, such as for diabetic retinopathy in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interfering with CCR3 ligation has been proposed as a therapeutic strategy for the treatment of allergic asthma with eosinophilia. However, a recent double-blind parallel-group study of 60 asthma patients with 94.9 % sputum eosinophils did not show a significant reduction in sputum or blood eosinophil counts or improvement of lung function [57]. These observations challenge the role of CCR3 in airway eosinophilia in asthma.…”
Section: Small Molecules Chemokine Receptor Antagonistsmentioning
confidence: 92%
“…The CC chemokine receptors CC chemokine receptor type 3 (CCR3) and CCR4 are G-protein-coupled receptors that are highly expressed in eosinophils and basophils, T H 1 and T H 2 cells, and airway epithelia. CCR3 and CCR4 act as receptors for a variety of chemokines including the eotaxins CCL5, CCL17, and CCL22, which play a role in asthma pathophysiology [23]. There is evidence that CCR3 inhibition may decrease inflammation, and CCR4 is believed to be able to recruit T H 2 cells to inflammatory sites [24].…”
Section: The Pathophysiology Of Asthmamentioning
confidence: 99%
“…GW 766994 is a selective, competitively binding CCR3 antagonist that has already completed phase I trials in patients with mild to moderate asthma and high sputum eosinophilia [23]. Mogamulizumab (AMG 761) is a humanized monoclonal afucosylated anti-CCR4 IgG1 antibody [82].…”
Section: Drugs Targeting Ccr3 and Ccr4mentioning
confidence: 99%